Caractérisation et Etude de l’Effet Antioxydant de Quelques Variétés de La Propolis Algériennes - GARMALA, SABRIA; OULD MOUSSA, KHADIDJA (My University, 2024)
Oxidative stress is a process that occurs in the body when free radicals damage cells and tissues. There is a wide range of options and approaches in the field of alternative therapies, such as Apitherapy. Propolis is a bee product composed of polyphenols that have a protective role against oxidative stress. The objective of our study is to determine the characterizations and evaluation of the antioxidant activity of three varieties of propolis (Tipaza, Khereddine, Ain Nouissy) by determining the propolis extraction yield, physicochemical analyses, qualitative analyses to determine the presence or absence of secondary metabolites, quantitative measurement of secondary metabolites, FT-IR spectrum analysis, and evaluation of antioxidant activity using three methods (DPPH free radical scavenging assay, FRAP iron reduction assay, and ABTS free radical scavenging assay). The analysis of the physicochemical parameters' results showed that the propolis from the three studied varieties meets international standards. The presence of secondary metabolites (polyphenols, flavonoids, tannins) in all three extracts was indicated by phytochemical analysis, and functional groups such as phenolic hydroxyl groups (OH), carbonyl groups (C=O), and amide groups (N- H) were detected by FT-IR spectrum analysis. The high polyphenol content in all three extracts indicates strong antioxidant activity. In conclusion, the propolis from the three studied varieties exhibits antioxidant activity.
Keywords: propolis; oxidative stress; FT-IR spectrum; antioxidant activity